Kelayakan Finansial Usaha Peternakan Ayam Broiler (Gallus Domesticus) Dengan Pola Kemitraan Di Kecamatan Seruway, Kabupaten Aceh Tamiang - Pratama, Riki; Mastuti, Rini; Jamil, Muhammad (Jurnal Penelitian Agrisamudra, 2025)
This study analyzes the income and financial feasibility of broiler chicken (Gallus domesticus) farming under a partnership system in Seruway District, Aceh Tamiang Regency. Using a quantitative approach with purposive sampling, data was collected from three key respondents (plasma farmers, Technical Service of PT. Satwa Sejahtera, and farm workers) through observation, interviews, questionnaires, and documentation. Data analysis using Microsoft Excel revealed total business revenue of IDR 265,178,235 annually (IDR 53,035,647 per production cycle), with income distribution of IDR 64,892,445 (plasma partners) and IDR 140,856,225 (core company) per year. Financial feasibility analysis demonstrated a Benefit-Cost Ratio (B/C Ratio) of 1.80 and Revenue-Cost Ratio (R/C Ratio) of 1.60 (both >1), confirming the business's financial viability and potential for further development.